2021
DOI: 10.3390/agronomy11040627
|View full text |Cite
|
Sign up to set email alerts
|

Recycled Wastewater and Reverse Osmosis Brine Use for Halophytes Irrigation: Differences in Physiological, Nutritional and Hormonal Responses of Crithmum maritimum and Atriplex halimus Plants

Abstract: Halophytes are capable of coping with excessive NaCl in their tissues, although some species may differ in their degree of salt tolerance. In addition, it is not clear whether they can tolerate other confounding factors and impurities associated with non-conventional waters. The experiment was performed in a greenhouse with Crithmum maritimum and Atriplex halimus plants, growing on soil and irrigated with two different water types: reclaimed wastewater (RWW) (EC: 0.8–1.2 dS m−1) and reverse osmosis brine (ROB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 69 publications
0
6
1
Order By: Relevance
“…Nutrient contents in different halophyte species were varied although they were cultivated in the same saline conditions, which could be due to the plant mechanism for salting stress conditions. The obtained results in this study were higher than those reported by Gómez-Bellot et al 30 , for Salicornia species. Based on the previous studies, the species of Salicornia and Halocnemum could accumulate the salts into epidermal vesicle bladders specialized in sodium sequestration, which could improve the tolerance of plants in salt-stress conditions 29 .…”
Section: Resultscontrasting
confidence: 86%
See 1 more Smart Citation
“…Nutrient contents in different halophyte species were varied although they were cultivated in the same saline conditions, which could be due to the plant mechanism for salting stress conditions. The obtained results in this study were higher than those reported by Gómez-Bellot et al 30 , for Salicornia species. Based on the previous studies, the species of Salicornia and Halocnemum could accumulate the salts into epidermal vesicle bladders specialized in sodium sequestration, which could improve the tolerance of plants in salt-stress conditions 29 .…”
Section: Resultscontrasting
confidence: 86%
“…Halophytes are efficient in adaptation and have a well-orchestrated mechanism for dealing with salinity stress 29 . In addition, they can complete their life cycle in saline conditions 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Gil et al [56] highlighted the effectiveness of plant antioxidant mechanisms against lipid peroxidation, while they also identified differences in the antioxidant defense machinery between different populations of C. maritimum. Gómez-Bellot et al [57] reported that the water status and photosynthetic activity was not impaired in Crithmum maritimum plants irrigated with brine, while the leaf content in Ca and B and 1-aminocyclopropane-1-carboxylic acid and trans-zeatin-glucoside increased under saline conditions. Moreover, according to Ciccarelli [30], sea fennel exhibits high resistance to drought stress due to the high water capacity of leaves, which is an important feature considering the impact of climate change on irrigation water availability.…”
Section: Sustainable Farming and Saline Agriculturementioning
confidence: 99%
“…Many studies have assessed the potential for using saline water on conventional crops and forages, however their low tolerance limits productivity (Jones et al, 2019;Romero-Trigueros et al, 2020). Thus, water desalinisation or application of irrigation water with a high salt concentration requires selection of appropriate species and genotypes (Gómez-Bellot et al, 2021). For example, Crithmum maritimum (sea fennel) and Atriplex halimus (Mediterranean saltbush) have recently been shown to tolerate irrigation by recycled wastewater and reverse osmosis brine but through differential accumulation of ions mediated by different hormonal signalling pathways (Gómez-Bellot et al, 2021).…”
Section: Salt Stress In Spacementioning
confidence: 99%
“…Thus, water desalinisation or application of irrigation water with a high salt concentration requires selection of appropriate species and genotypes (Gómez-Bellot et al, 2021). For example, Crithmum maritimum (sea fennel) and Atriplex halimus (Mediterranean saltbush) have recently been shown to tolerate irrigation by recycled wastewater and reverse osmosis brine but through differential accumulation of ions mediated by different hormonal signalling pathways (Gómez-Bellot et al, 2021). Both species can be of use for humans but C. maritimum, may be of particular use on space missions an additional food source, and with leaves exhibiting aromatic and medicinal purposes as a tonic and diuretic (Ruberto et al, 2000).…”
Section: Salt Stress In Spacementioning
confidence: 99%